Design and Evaluation of UI/UX Using the Heuristic Evaluation Method: The Case of Universitas Papua Website - Natasya Yusinta Subay; Dedi I. Inan; Ratna Juita; Marlinda Sanglise; Devid Riswandy Podajow (G-Tech: Jurnal Teknologi Terapan, 2024)
This research focuses on designing and evaluating user interface/user experience (UI/UX) of the Informatics Engineering website profile of Papua University using the Heuristic Evaluation method. One crucial aspect of website design is the UI design, which serves as the interaction tool between the user and the website itself, thus determining the user experience. The research method includes problem identification, literature review, UI design, questionnaire testing, evaluation, and result analysis. The questionnaire as a tool for the evaluation obtained data from 21 respondents, including 4 lecturers of Informatics Engineering experiencing in this field. The analysis concludes that there is an average severity level of 2, indicating minor issues in the website UI design. Aspects requiring further improvement include Error Prevention System, Recovery and System, and Help and Documentation. However, these aspects can still be improved to enhance the quality of website design. Suggestions for further development include adding error message notification features, feedback features, and design documentation to enhance user experience when using the website.